Pneumonia and Pleural Empyema due to a Mixed Lactobacillus spp. Infection as a Possible Early Esophageal Carcinoma Signature - Chaini, Eleftheria; Chainis, Nikolaos D.; Ioannidis, Anastasios; Magana, Maria; Nikolaou, Chryssoula; Papaparaskevas, Joseph; Liakata, Melina-Vassiliki; Katopodis, Panagiotis; Papastavrou, Leonidas; Tegos, George P.; Chatzipanagiotou, Stylianos (Frontiers in Medicine, 2016)
Lactobacilli are human commensals found in the gastrointestinal and genitourinary tract. Although generally conceived as non-pathogenic microorganisms, the existence of several reports implicating them in certain severe pathological entities renders this species as opportunistic pathogens. The case of a 58-year-old woman with mixed Lactobacillus infection is described. The patient was admitted in an outpatient clinic with community acquired pneumonia and on the third day of hospitalization she presented rapid pneumonia deterioration. Subsequent imaging techniques revealed increased pleural empyema in alignment with the general deterioration of her clinical condition. Pleural fluid culture revealed the presence of Lactobacillus delbrueckii and L. gasseri and the infection was successfully treated with clindamycin. Five months after hospital discharge and an overall good condition, the patient developed signs of dysphagia and upon re-admission an inoperable esophageal carcinoma was diagnosed. The patient succumbed to the cancer eleven months later. Herein, we report for the first time a mixed respiratory infection due to lactobacilli, associated with a formerly unveiled esophageal malignancy.